2011
DOI: 10.1016/j.cub.2011.08.059
|View full text |Cite
|
Sign up to set email alerts
|

Nonretinotopic Exogenous Attention

Abstract: Summary Attention is crucial for visual perception because it allows the visual system to effectively use its limited resources by selecting behaviourally and cognitively relevant stimuli from the large amount of information impinging on the eyes. Reflexive, stimulus-driven attention is essential for successful interactions with the environment because it can, for example, speed up responses to life threatening events. It is commonly believed that exogenous attention operates in the retinotopic coordinates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 38 publications
4
30
0
Order By: Relevance
“…A recent study by Boi et al (2011) had also cast some doubts on the strict retinotopy of exogenous attention. Boi et al used a cuing paradigm in which the exogenous cue (an abrupt onset) was followed by a variant of the Ternus-Pikler display in which three squares appeared to move laterally in tandem as a group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Boi et al (2011) had also cast some doubts on the strict retinotopy of exogenous attention. Boi et al used a cuing paradigm in which the exogenous cue (an abrupt onset) was followed by a variant of the Ternus-Pikler display in which three squares appeared to move laterally in tandem as a group.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these findings point to a possible role for objectcentered attention in exogenous spatial cueing (see also Boi, Vergeer, Ogmen, & Herzog, 2011). The present study was designed to determine whether the classic Posner exogenous cuing effect possibly operates in nonretinotopic coordinates.…”
Section: Exogenous Object-centered Attentionmentioning
confidence: 99%
“…No differences were found on the error rates. Clearly, these results reveal a frame-centered priming effect that cannot be explained by working memory (Hollingworth, 2007;Jiang et al, 2000) or attentional learning (Barrett et al, 2003;Boi, Vergeer, et al, 2011;Umilta et al, 1995). In short, frame-centered priming reflects both low-level visual featural representation and high-level identity representation.…”
Section: Level Of Representations During Frame-centered Primingmentioning
confidence: 84%
“…Previous studies show that one can voluntarily direct attention to a remote, frame-centered location (Barrett, Bradshaw, & Rose, 2003;Boi, Vergeer, Ogmen, & Herzog, 2011;Umilta, Castiello, Fontana, & Vestri, 1995) and learn to allocate attention to a relative location within a frame (Kristjansson, Mackeben, & Nakayama, 2001;Maljkovic & Nakayama, 1996; C. R. Olson & Gettner, 1995), but empirical evidence for automatic frame-centered object representation is bleak, perhaps owing to the challenge in isolating frame-centered processes from object-based (framebased) and space-based processes. Our conceptual approach to isolating frame-centered effect is to (a) present two preceding or trailing objects on the same frame and equidistant from the target, effectively controlling object-based (frame-based) effect and space-based effect, and (b) manipulate the target's relative location within its frame.…”
Section: Introductionmentioning
confidence: 98%
“…These predictions have also been tested formally, and the results lend further support to the RFMF theory (Aydın et al, 2008). Moreover, why and how attention is allocated to moving stimuli (Boi et al, 2009;Boi, Vergeer, Öğmen, & Herzog, 2011) and why masking is retinotopic but form perception can escape masking when a motion is predictable are other predictions of the RFMF theory that we have recently tested experimentally (Noory, Herzog, & Öğmen, in press), and we have demonstrated that RFMF can be implemented computationally to explain data at the quantitative level (Clarke et al, 2015).…”
Section: Discussionmentioning
confidence: 52%